Tensile-strained micromechanical resonators made from crystalline InGaP with low mechanical dissipation and high optical reflectivity - Fia, Hellman (My University, 2022)
The interest in micro- and nanomechanical resonators has grown rapidly during the last decade due to their broad applicability within metrology and fundamental science. They have, for instance, been brought to the quantum regime and have also been demonstrated to be incredibly precise detectors of small masses, forces, or displacements. A micromechanical resonator’s motion can be detected via optical means, where the resonator’s reflectivity enhances the coupling between it and the light —– resulting in a more efficient read-out. High-reflectivity micromechanical resonators can be achieved by alternating their in-plane dielectric constants with structures known as photonic crystals. On the other hand, a precise read-out of the resonator’s displacement requires low mechanical dissipation for the measurement signal to exceed the thermal noise floor. Dissipation can be minimized by carefully selecting the appropriate material, design, and operating environment for the resonator. Furthermore, mechanical dissipation can even be diluted by introducing tensile strain to the material, which acts as additional storage of energy. The quality factor, which is the ratio between the total energy stored in the system and energy lost during one cycle, is commonly used to quantify mechanical dissipation. This thesis uses highly tensile strained crystalline InGaP to realize micromechanical resonators with low mechanical dissipation. Crystalline materials are promising candidates for highly sensitive micromechanical resonators due to their potentially low intrinsic dissipation, high intrinsic strain, and yield strength. The first part of this thesis investigates the first two of these properties for InGaP by comparing fabricated doubly-clamped strings with analytical models. It was inferred that the stress depends on the crystal direction and varies between 200-500 MPa. Further, the InGaP used in this thesis shows an intrinsic quality factor between 5700±1000 up to 7900 ± 1700. The second part of this thesis focuses on optimizing the geometry of trampoline-shaped micromechanical resonators to enhance their mechanical quality factor and their optical reflectivity. An improved optical reflectivity was observed for fabricated devices patterned with a photonic crystal. FEM-based simulations were made to find dimensions of the trampoline that considerably reduce mechanical clamping loss to the surrounding supporting structure. Implementing these designs to trampoline-shaped micromechanical resonators showed a quality factor of 7 · 10^6 at low temperatures, which was not limited by clamping loss. It was instead demonstrated that the quality factor was limited by gas damping. The mechanical and optical properties of micromechanical resonators fabricated from crystalline InGaP demonstrated in this thesis have shown promising results and provide all requirements for the resonators to be used in optomechanical systems in the near future.
Keywords: MEMS; mechanical systems; optomechanics; InGaP; nanomechanics; nanophotonics